Sensitivity of Awaji Criteria and Revised El Escorial Criteria in the Diagnosis of Amyotrophic Lateral Sclerosis (ALS) at First Visit in a Tunisian Cohort - Bademain Jean Fabrice Ido; Imen Kacem; Mahamadi Ouedraogo; Amina Nasri; Saloua Mrabet; Amina Gargouri; Mouna Ben Djebara; Bawindsongré Jean Kabore; Riadh Gouider (Neurology Research International)
Background. Amyotrophic lateral sclerosis (ALS) is a fatal disease whose diagnosis and early management can improve survival. The most used diagnostic criteria are the revised El Escorial criteria (rEEC) and Awaji criteria (AC). The comparison of their sensitivities showed contradictory results. Our study aimed to compare the sensitivities of these two criteria in the diagnosis of definite ALS, at first visit, in a Tunisian hospital cohort. Materials and Methods. This was a retrospective study including 173 patients diagnosed with ALS at the Department of Neurology of the Razi Hospital between January 2003 and April 2018.After studying the clinical features of the disease in our study population,each patient was categorized according to the rEEC and AC based on data collected in his medical record during his first visit to our department. Then, we compared the sensitivities of these two criteria in the diagnosis of definite ALS. Results. Our Tunisian cohort was characterized by a slower disease progression. The sensitivity of the AC (69.4%) was significantly higher than that of the rEEC (40.5%) (p < 0.001). When the clinical signs evolved for less than 6 months, the sensitivities were 61% for AC and 12% for rEEC (p < 0.001). After 24 months of disease progression, the sensitivities were 78.2% for AC and 69.1% for rEEC (p = 0.063). It was impossible to categorize seventeen patients by the two criteria. Conclusion. Our study demonstrated that patients in AC are more sensitive than rEEC in the early diagnosis of ALS in our Tunisian cohort. However, this superiority is gradually reduced during the evolution of the disease.